2022
DOI: 10.1002/fsn3.2850
|View full text |Cite
|
Sign up to set email alerts
|

Genetic characterization and quantitative trait relationship using multivariate techniques reveal diversity among tomato germplasms

Abstract: Tomato accessions collected from different sources were evaluated to study their diversity, genotype–traits association, as well as pinpoint most selective trait(s) in a controlled environment in Jimma, Ethiopia. The two terms pot experiments were carried out in randomized complete block design with three replications. The genotype–trait (GT) biplot revealed high percentage variability above 70% in related growth traits for the first and second principal components (PC) summed up, in the two trials, whereas re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 55 publications
(58 reference statements)
2
3
0
Order By: Relevance
“…The noteworthy amount of the T × T interaction observed implies both additive and crossover interactions in our dataset, indicating differential rankings of measured traits across treatments. This finding aligns with similar observations in other plant studies (Woyann et al, 2019;Ene et al, 2022;Fantahun et al, 2023), highlighting the challenge of achieving an indirect response to selection overall treatments without considering the T × T interaction.…”
Section: Resultssupporting
confidence: 92%
“…The noteworthy amount of the T × T interaction observed implies both additive and crossover interactions in our dataset, indicating differential rankings of measured traits across treatments. This finding aligns with similar observations in other plant studies (Woyann et al, 2019;Ene et al, 2022;Fantahun et al, 2023), highlighting the challenge of achieving an indirect response to selection overall treatments without considering the T × T interaction.…”
Section: Resultssupporting
confidence: 92%
“…According to the authors, the lack of structure among the lines could be credited to the parents, which were diverse from each other. However, the population structure pattern observed in F3 and BC1F2 composite populations in the present study followed the relatedness found among the recurrent parents in an earlier genetic characterization study (Ene et al 2022). The closeness in relationship among the recurrent parents could have contributed to the observed population structuring pattern among the lines.…”
Section: Clustering Pattern Analysissupporting
confidence: 80%
“…It could be suspected that the genetic distance between the parental lines that generated lines of these clusters that showed overlapping are similar. Ene et al (2022) reported the grouping of the recurrent parents of clusters D (CLN2498D) and U (UC Dan INDIA) in the same cluster while those of clusters H (CLN2417H) and T (Tima) in the same cluster showing a level of relatedness. Although each cluster was of different interspecific cross, they were half sib progenies sharing a common parent (pollen donor-wild parent 'LA2093') from the initial cross.…”
Section: Clustering Pattern Analysismentioning
confidence: 99%
“…Te domesticated accessions were four morphologically diverse materials. Two divergent parents included; "CLN2498D" (D) and "CLN2714H" (H) sourced from Ethiopia as well as "UC Dan INDIA" (U) and "Tima" (T) from Nigeria were used as characterized by Ene et al [25] in terms of superiority and weakness in the quantitative traits. "CLN2498D" and "UC Dan INDIA" were superior performing parents in terms of fruit size (round and large) and fruit yield but had fewer fruit numbers and lacked resilience to humid environmental conditions whereas "CLN2714H" and "Tima" were the weaker performers in terms of fruit yield, fruit number; had elongated medium fruit size, and took longer days to achieve the phenological traits.…”
Section: Plant Materialsmentioning
confidence: 99%